Le tourisme scientifique dans les Alpes françaises : un laboratoire pour la médiation scientifique et la recherche - Yannick Vialette; Pascal Mao; Fabien Bourlon (Revue de Géographie Alpine)
This contribution focuses on scientific mediation implemented within scientific tourism initiatives in mountain areas. Three case studies in the French Alps support this research: the Jardin Alpin du Lautaret of the University of Grenoble Alpes, the CREA Mont-Blanc, a private research center organizing participatory science and student travel abroad programs and the scientific hut to hut trekking routes in the Ecrins National Park, organized jointly with a scientific research project (Labex ITEM, Reflab). Scientific tourism and mediation are first defined. Next, a quantitative and qualitative approach (with interviews and participant observations) allows us to understand the impact and role of scientific mediation within tourism. Results show a high level of interest of the issue within involved publics and a close connection between experience and knowledge. It appears that it is also a tool for public awareness of the challenges of our modern societies.